"Farm size, resource-use efficiency and income distribution" - "Saini, G. R." (New Delhi, 1979)
The ability of agriculture to contribute directly to economic growth and to the welfare of farm families is dependent on the level of farm incomes and the resultant surpluses in the agricultural sector. In determining the existing oppurtunities in agriculture for economic growth, we ask ourselves the question : Can farmers in low income communities substantially increase farm incomes and the resultant surpluses by an efficient allocation of the agricultural factors of production presently at their disposal ?Given the resources at their command and the knowledge of production possibilities, if farmers are not efficient in the use of their resources, there certainly exists an unexploited potential for increasing farm incomes and surpluses which can serve as an inexpensive sources of further economic growth.
Keywords: Agriculture-Economic aspects